Post-caldera pumice cones of the Payún Matrú caldera, Payenia, Argentina: Morphology and deposits characteristics. (March 2019) - Hernando, I.R.; Petrinovic, I.A.; D'Elia, L.; Guzmán, S.; Páez, G.N.
Abstract: The formation of pumice cones by deposition of near-vent pumice fragments is relatively rare in comparison with the occurrence of their mafic equivalents, the scoria cones. The Quaternary Payún Matrú caldera (36° S, 69° W), within the back-arc of the Southern Volcanic Zone of the Andes (Argentina), presents several trachytic pumice cones developed during its post-caldera stage and distributed mostly along the southeastern to northwestern caldera rim. These cones are spatially and temporally related to domes and lava flows of similar composition. Given the good preservation of pumice cones in Payún Matrú, exposures of their internal deposits are observed sporadically and are restricted to the outer zone of the cone, whereas the core deposits of the cone are unexposed. Magma fragmentation was likely purely magmatic, as indicated by the clast sizes of the juvenile fragments and the low abundance of basement-derived lithic clasts. Three distinct facies were defined: non-welded facies, moderately welded facies, and densely welded facies. The non-welded facies are interpreted as near-vent fall deposits formed by accumulation of ballistic ejecta and by deposition of clasts derived from the jet/lower plume regions in low energy explosive events. The moderately welded facies presents dense and relatively vesicular domains, suggesting a formation by the agglutination of spatter upon landing. The densely welded facies, with a banded lava-like appearance, indicates their formation by a high deposition rate at high temperatures in a fire fountain-like eruption of low viscosity trachytic magma. Lapilli sized fall deposits found outside the caldera that may be linked to pumice cones, suggest the occasional development of a more explosive eruption pulse/s (violent strombolian to subplinian). Highlights: Pumice cones represent near-vent fall deposits of pumice and glassy bombs/blocks. Non-welded to densely welded facies were recognized in pumice cones deposits. Pumice clasts are trachytic as other contemporaneous post-caldera lavas and domes. Eruptive styles were from low energy explosive events to fountain-like eruptions.